Female participation and corruption in the public sector. (1st October 2016) - Jin, Jongsoon
Abstract: The purpose of this study is to contribute toward building an empirical foundation for enhanced female participation in the public sector. Specifically, this article provides empirical evidence on how female participation affects corruption level in the public sector with ordinary least square (OLS) and generalized least squares (GLS) analyses of 120 countries using panel data (from 2000 to 2010), with increased statistical validity. The results of the analyses show that female participation lowers the level of corruption in the public sector. This implies that public personnel administration, especially human resource planning, needs to be strategically designed to increase female participation from a corruption control perspective.